Impact of family farming: A case of vegetable cultivation under Farmer FIRST Programme - Singh, Kuldeep; Romana, Buta Singh; Kumar, Pankaj; Singh, Dalbeer (Indian Farming, 2022)
The continuous decline in the farm size is making it difficult to make a comfortable living from conventional agriculture for marginal and small farmers. Vegetable cultivation is potential candidate to help these farmers to make a way towards prosperous living. Despite the potential benefits of this enterprise, marginal and small farmers hesitate to opt for vegetable cultivation due to its technical and managerial obstacles for an individual farmer. But the family approach can be a ray of hope in this regard through which farmers can accumulate the economic and social resources to harness full advantage of vegetable cultivation. This article highlights the story of a such joint family of Sh. Vinder Singh, who emerged as the torch bearer of family approach in vegetable cultivation. With the adoption of high yielding varieties/hybrids, low cultivation technique, hybrid seed and nursery production of vegetable crops, his family was able to multi-fold their income (about `2.64 lakh/acre) and also became exemplary of family cohesiveness for community.